Pengaruh Tapas Acupressure Technique terhadap Tingkat Kecemasan pada Pasien Hipertensi - Putu Mitha Eka Gayatri; I Nengah Sumirta; I Gede Widjanegara (Jurnal Gema Keperawatan, 2022)
Hypertension is chronic disease that impact the patient's psychology. Treatment tends to be long and risk complications causes hypertension patients experience anxiety. High levels of anxiety affect self-care management and medication. The aims of research to determine effect of Tapas Acupressure Technique to level anxiety hypertension patients in work area of UPT Puskesmas Kuta Utara on 2021. This research used method pre-experimental design with one group pre-post test. Sampling using non-probability with purposive sampling. The number samples was 19 subjects. The normality test uses Shapiro-Wilk. Hypothesis using Wilcoxon Signed Rank Test. The research instrument used Hamilton Anxiety Rating Scale (HARS). The research was in March-April for 1 month. The results showed before given Tapas Acupressure Technique most the respondents experienced mild anxiety 13 people (68.4%) and moderate anxiety 6 people (31.6%). After the treatment, level of anxiety decreased, there was no anxiety 5 people (26.3%), 12 people mild anxiety (63.2%), and 2 people moderate anxiety (10.5%). After analyzed, the p-value 0.000 alpha 0.05. The conclusion that there is effect of Tapas Acupressure Technqiue on anxiety level hypertension patients in work area of UPT Puskesmas Kuta Utara on 2021, meaning that Tapas Acupressure Technique can reduce anxiety level of hypertension patients. Recommendations For health care providers to apply the Tapas Acupressure Technique to patients with hypertension to reduce anxiety so that it can lower blood pressure.